Functional analysis of LAP2 beta, gamma and o during the development of zebrafish (Danio rerio) - Beauvais, Ariane (University of Ottawa (Canada), 2003)
Three isoforms of the lamina-associated polypeptide 2 (LAP2) family, have been identified in zebrafish (Danio rerio). Zebrafish LAP2 (ZLAP2) beta, gamma and o have identical aminoterminal regions containing the LEM domain. A lamina binding domain and a membrane spanning sequence are also present in the carboxyterminal region. The maternally synthesized ZLAP2o is the biggest of the three isoforms and is detected as a polypeptide of Mr 84 000. The somatic isoforms, ZLAP2beta and gamma are represented as smaller polypeptides of Mr 66 000 and 45 000 respectively. Western and northern blot analysis indicated that ZLAP2o is the only LAP2 present in early embryonic stages up to the gastrula stage. With the progression of embryonic development, the amount of ZLAP2o decreased whereas the amount of somatic isoforms ZLAP2beta and gamma) increased. Using immunofluorescence on somatic cells, ZLAP2beta and gamma are observed at the nuclear periphery in interphase cells. A cytoplasmic distribution appeared in late prometaphase and the isoforms are located at the surface of segregated chromosomes in late anaphase. However, during early embryonic development, ZLAP2o is associated with mitotic chromosomes prior to anaphase and the formation of karyomere is also observed. Using the morpholino technology, knock-down experiments on ZLAP2 during the zebrafish development suggest a strong correlation between the loss of ZLAP2 expression and abnormal phenotypes observed 24 hours post-fertilization. Altogether, my data indicate that ZLAP2 proteins may play a key role in early developmental events.
Keywords: Biology, Cell.